2020
DOI: 10.1002/agj2.20337
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic assessment of cover cropping and tillage practices across environments

Abstract: Cover crops (CCs) are considered one of the few agronomic strategies to help reduce environmental pollution, while improving soil properties. However, the use of tillage could negate those benefits entirely. Therefore, the goal of this study was to monitor soil properties and cash crop yields from five different CC rotations compared to fallow controls throughout Illinois. A split-block arrangement of tillage (chisel tillage vs. no-till) and CC rotations (six levels) in a randomized complete block design with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
1
12
1
Order By: Relevance
“…Moreover, the high CEC of the present study's soil indicated a greater buffering capacity against pH changes ( Table 1). This innately high CEC would be resilient against changes from CC and tillage [13]. Indeed, a past meta-analysis on CC effects on soil properties reported smaller percentage changes in CEC than those of our results, but the differences in CEC were still not statistically significant [63].…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…Moreover, the high CEC of the present study's soil indicated a greater buffering capacity against pH changes ( Table 1). This innately high CEC would be resilient against changes from CC and tillage [13]. Indeed, a past meta-analysis on CC effects on soil properties reported smaller percentage changes in CEC than those of our results, but the differences in CEC were still not statistically significant [63].…”
Section: Discussioncontrasting
confidence: 69%
“…Unlike the shifts in the soil microbiome we detected, chemical soil properties were only marginally influenced by cover crop rotations and tillage practices, partially because of the innate buffering capacity of the rich Mollisols across the region [13,14,58]. Soil NO 3…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations